2020
DOI: 10.1021/acscatal.0c02941
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Understanding of the Pd(0)-Catalyzed Coupling Cyclization of 1,2-Allenyl Ketones with Aryl Halides: A Computational Study

Abstract: The Pd­(0)-catalyzed coupling cyclization of 1,2-allenyl ketones with aryl halides to construct multisubstituted furan derivatives has been developed. Nevertheless, the detailed mechanism of this reaction, proceeding via either the Pd­(II)-carbenoid or the π-allyl-Pd­(II) intermediate, still remains debatable. Herein, computational studies were performed to provide mechanistic insights into the reactions, and substituent-dependent mechanistic pathways were revealed. Computational results suggest that the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 132 publications
0
5
1
Order By: Relevance
“…The above results indicate that for the substituted 1,2-allenyl ketone, the π-allyl-Pd( ii ) intermediate mechanism with an energy barrier of 27.7 kcal mol −1 may mainly contribute to the formation of the product and the Pd( ii )-carbenoid intermediate mechanism also makes partial contributions. This situation is different from the reactions of the substituted 1,2-allenyl ketones with aryl halides reported recently by Bao et al , 28 who showed that the Pd( ii )-carbenoid intermediate mechanism is beneficial when the aryl reagent is aryl iodide rather than the present aryl boronic acid.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…The above results indicate that for the substituted 1,2-allenyl ketone, the π-allyl-Pd( ii ) intermediate mechanism with an energy barrier of 27.7 kcal mol −1 may mainly contribute to the formation of the product and the Pd( ii )-carbenoid intermediate mechanism also makes partial contributions. This situation is different from the reactions of the substituted 1,2-allenyl ketones with aryl halides reported recently by Bao et al , 28 who showed that the Pd( ii )-carbenoid intermediate mechanism is beneficial when the aryl reagent is aryl iodide rather than the present aryl boronic acid.…”
Section: Resultscontrasting
confidence: 82%
“…To account for these intra-and intermolecular crosscoupling reactions, the previous reports have proposed two different mechanistic pathways, which can be referred to as the metal-carbene intermediate mechanism [18][19][20] and the π-allyl-metal intermediate mechanism. 26,27 Bao et al 28 have reported an elegant DFT-based computational study on the cross-coupling reaction of 1,2-allenyl ketones with iodobenzene, one of the most commonly used aryl halides. It is found that the viable mechanistic pathway depends on the substituents on either 1,2-allenyl ketones or iodobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…Sakaki et al employed this method to calculate the free-energy profiles of a series of transition metal catalytic reactions, e.g., the migratory insertion reactions CO 2 , 185,186 borylation, 187,188 [2 + 2] and [4+2] oxidative cyclization reactions, 189,190 and oxidative addition/reductive elimination reactions. [191][192][193][194][195] In addition, Guan,196,197 Bao, [198][199][200] Huang, 201 and Lei 202 applied this model to investigate the reaEction mechanisms and free-energy profiles of catalytic reactions.…”
Section: Entropy Correction In the Solution Systemmentioning
confidence: 99%
“…On the other hand, electron-donating aryl halides favour the π-allyl reaction intermediates 164, producing same intermediates 165 after oxycyclization (Scheme 32b). [110] A related palladium carbene intermediate 169 has been also proposed to explain the cross-coupling reaction of allenones 2 and boronic acids 167 to synthesize 3-substituted furans 168 (Scheme 33a). [111] Both aryl and allyl boronic acids have provided good results, and allenones showing a wide range of substitution pattern have been effective for this transformation, building highly substituted furans with good yields (Scheme 33a).…”
Section: Synthesis Of Furansmentioning
confidence: 99%
“…Allenones 2 exhibiting alkyl or aryl substituents at the terminal allenic position, or showing steric hindrance in R 2 or R 3 positions are more likely to evolve through a palladium carbenoid intermediate 164 , which generates the observed furans after migratory insertion building dihydrofurans 165 and eventual β‐elimination. On the other hand, electron‐donating aryl halides favour the π‐allyl reaction intermediates 164 , producing same intermediates 165 after oxycyclization (Scheme 32b) [110] …”
Section: Synthetic Utilitymentioning
confidence: 99%